Synthesis of ZnO/CNT Nanocomposites for Ultraviolet Sensors - Basit, Maryam; Abbas, Murrawat; Ahmad, Naeem; Javed, Sofia; Shah, Nazar Abbas (Frontiers in Materials, 2022)
Zinc oxide/carbon nanotube (ZnO/CNTs) nanocomposites are developed on gold (Au)-coated unpolished Si p-type (100) substrates with 2, 4, 6, 8, and 10 nm thicknesses by vapor–liquid–solid method. One set of Au-coated Si substrates are annealed to develop Si–Au samples for better nucleation. XRD, FE-SEM, Raman, and photoluminescence spectroscopic characterizations are used to study structural, morphological, and optical properties on annealed and unannealed catalyst layers with various Au thickness samples. In XRD results, the ZnO/CNT nanocomposites are observed with higher crystallinity and purity of phase. FE-SEM images showed variety of nanostructures with variation in morphologies with respect to Au thickness in annealed and unannealed samples. Clear indication of high defect concentrations and high crystallinity is observed in Raman spectra. It is observed in PL spectra that preferred peak orientation with shift ∼4 nm in the unannealed Au layer and ∼9 nm in annealed Au layer samples exhibited formation of ZnO/CNT nanocomposites. Efficient sensing is observed in the 6-nm thickness Au layer in the unannealed sample. Annealed Au-coated Si samples at 8 and 10 nm thicknesses showed efficient UV sensing with quick response and recovery time.